Co-delivery of gambogic acid and TRAIL plasmid by hyaluronic acid grafted PEI-PLGA nanoparticles for the treatment of triple negative breast cancer. (1st January 2017) - Wang, Shengpeng; Shao, Min; Zhong, Zhangfeng; Wang, Anqi; Cao, Jiliang; Lu, Yucong; Wang, Yitao; Zhang, Jinming
Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-based combination therapy and gene therapy are new strategies to potentially overcome the limitations of TRAIL, however, the lack of efficient and low toxic vectors remains the major obstacle. In this study, we developed a hyaluronic acid (HA)-decorated polyethylenimine-poly(d, l -lactide-co-glycolide) (PEI-PLGA) nanoparticle (NP) system for targeted co-delivery of TRAIL plasmid (pTRAIL) and gambogic acid (GA) in triple-negative breast cancer (TNBC) therapy. GA was encapsulated into the core of the PEI-PLGA NPs while pTRAIL was adsorbed onto the positive NP surface via charge adsorption. The coating of HA on PEI-PLGA NPs functions as a targeting ligand by binding to CD44 receptor of TNBC cells and a shell to neutralize the excess positive charge of inner NPs. The resultant pTRAIL and GA co-loaded HA-coated PEI-PLGA NPs exhibited spherical shape (121.5 nm) and could promote the internalization of loaded cargoes into TNBC cells through the CD44-dependent endocytic pathway. The dual drug-loaded NPs significantly augmented apoptotic cell death in vitro and inhibited TNBC tumor growth in vivo . This multifunctional NP system efficiently co-delivered GA and pTRAIL, thus representing a promising strategy to treat TNBC and bringing forth a platform strategy for co-delivery of therapeutic DNA and chemotherapeutic agents in combinatorial TNBC therapy.